Analysis Of Factors And Influence Of The Covid-19 Pandemic On The Completeness Of Basic Immunization In Under-Fives In The Working Area Of Cibuaya Puskesmas 2020 – 2021 - Rahayu, Mianita; Eka S, Titin (International Journal of Health and Pharmaceutical (IJHP), 2023)
Background: Immunization is the most effective and efficient public health effort in preventing several dangerous diseases. History has recorded the enormous role of immunization in saving the world's people from illness, disability and even death due to diseases such as Smallpox, Polio, Tuberculosis, Hepatitis B which can result in liver cancer, Diphtheria, Measles, Rubella and Congenital Rubella Syndrome. Syndrome/CRS), Tetanus in pregnant women and newborns, Pneumonia (pneumonia), Meningitis (inflammation of the lining of the brain), to Cervical Cancer caused by Human Papilloma Virus infection. Research Objectives: to find out the Factor Analysis and Influence of the Covid-19 Pandemic on the Completeness of Basic Immunization in Toddlers in the Working Area of the Cibuaya Health Center in 2020 – 2021. Research Method : Analytical with cross sectional approach. The sample in this study at the Cibuaya Health Center in November 2022 was 75 people (total sampling). Research results: The influence of educational factors (p value = 0.021), employment factors (p value = 0.002), availability of facilities (p value = 0.000), health facility support factors (p value = 0.014), family factors (p value = 0.011) with the completeness of basic immunization on toddlers. Conclusions and Suggestions: It is hoped that the puskesmas will provide more intensive education, for example health programs through posyandu. For respondents with low education, they are not preoccupied with household work.